Latin-American Society Of Forensic Genetics (SLAGF) results of the Interlaboratory Quality Control Exercise 2010-2011 - Cicarelli, Regina Maria Barretto [UNESP]; De Castro, M.; Vela, M.; Aguirre, V.; Morejon, G.; Burgos, G.; Valenzuela, G.; Builes, J. J.; Gaviria, A. (Elsevier, 2011)
Latin-American Society of Forensic Genetics (SLAGF) Interlaboratory Quality Control Exercise (2010-2011) included the analysis of three bloodstain samples in FTA Classic Card (three persons, biologically unrelated) and one theoretical exercise. There were 56 participating laboratories from 13 Latin-American countries that belong to society, were reported 70 STRs, including autosomal and sex chromosome markers with consensus in 53 STRs with a rate in reporting errors of 2.3%. Fifty-six laboratories reported results in theoretical exercise with mistakes in calculation of IP for each marker. It is necessary to hold meetings to discuss the results of this exercise to reach conclusions and recommendations on all aspects of DNA forensics analysis and paternity test, to improve results and quality in the results of each laboratory. © 2011 Elsevier B.V.
Keywords: DNA; Latin-America; Quality Control Exercise; SLAGF; amelogenin; autosome; blood analysis; blood sampling; DNA determination; forensic genetics; genetic marker; human; laboratory test; paternity test; priority journal; quality control; sex chromosome; short tandem repeat